DEVELOPING THE THEORETICAL RESOURCE MODEL FOR REFUGEE STUDENT INTEGRATION - Hayrapetyan, Davit; Hakobjanyan, Anna; Mirzoyan, Narine (Modern Psychology, 2024)
In 2023, more than 100,000 Artsakh residents were forced to leave their homes and were forcibly displaced to the Republic of Armenia. Adaptation of forcibly displaced people to a new environment and integration into society is one of the primary research issues facing us today. The process of adaptation and integration of Artsakh residents is endowed with a number of features, which are determined by a number of objective and subjective factors. Several conceptual models of refugee integration have been developed in science and practice. In this article, we discuss some key models. Taking into account that the forced displacement of Artsakh residents, unlike many existing examples, has some peculiarities, and also there are no universal models of integration of refugee students, we developed and proposed a resource-based model of integration of refugee students. In this model, we have identified personal and environmental factors that, breaking into the resource base of the refugee person, condition the efficiency of integration. Among personal factors, we consider two groups of factors. The first is the group of socio-economic and demographic factors. The second group of personal factors is psychological, in which we consider personal perceptions and evaluation of possible risks and dangers. Environmental factors include refugees’ participation and citizenship and rights of a person. According to our proposed approach, these factors are reflected in the resource environment of the refugee personality. According to our approach, the core of a student’s resource environment is a person’s time perspective and also we emphasize being in the educational process as the most important resource in the integration process. The next resource is a person’s perception and assessment of their own level of well-being.